دور المجالس الاستشارية البلدية في تفعيل التنمية الاقتصادية المحلية دراسة حالة البلدية النموذجية * أولاد بن عبد القادر* – ولاية الشلف –: The role of municipal advisory councils in activating local economic development Case study of the model municipality - Ouled Ben Abdelkader - *Chlef Province* - بلبراهيم جمال (Journal of North African Economies, 2025)
Through this research paper, we aim to highlight and present one of the most important international partnership experiences that Algeria has undergone in the context of its adoption of the new management trends that the Algerian state seeks to establish in the management of public affairs across various levels, fields and sectors. The case relates to adopting the participatory democracy approach as an innovative mechanism that serves to achieve The required local development. Talking about local development is associated with the preparation and embodiment of the contents of municipal development plans, which are considered the reference for projects that respond to the requirements of the population, and in accordance with the methodology of the Capdel program that was applied in the model municipality of Ouled Ben Abdelkader, where the approach to the contribution of civil society with its various actors in management was adopted. Local participation by structuring it within the so-called Municipal Advisory Council, which is considered the first official experience in the practices of local groups, as the latter worked with the Municipal People’s Council to formulate the municipal plan of a generation according to an innovative and comprehensive methodology. As a result of this research paper, the methodology of the “CAPDEL” partnership program can be considered as the best international participatory management methodologies that will give a qualitative leap in the practices of local groups that will respond to the requirements of local development, and this is if what is stated in the municipal development plan for a new generation is applied on the ground.